Efforts to Improve Discipline Through Group Guidance Services for Class XI IPS Students of SMA Negeri 39 Jakarta - Nilawati, Raden Roro Baiduri; Jamal, Yuliana; Darsono, Deira Razzaaq (Journal of Social Research, 2023)
The research addresses disciplinary issues among students, focusing on rule violations such as incomplete attributes, tardiness, and late return after breaks. The objective is to enhance discipline through group guidance. Employing a classroom action research method with Counseling Guidance (PTBK), the study involves a population of 32 students, with a purposive sampling technique selecting 12 participants. Data collection utilizes questionnaires and observation sheets. Qualitative analysis involves comparing discipline observations from cycle I to cycle II, while numerical data undergoes comparative descriptive analysis across initial conditions, cycle I, and cycle II. The findings reveal that group guidance significantly improves the discipline of Class XI.IPS students at SMA NEGERI 39 JAKARTA. Prior to intervention, 12 students lacked discipline, with a target improvement of 40% (6 students). In cycle II, the average score rose to 82.91 (74.03%), surpassing the target with a notable increase in discipline among 6 students: SSP (22.32%), RTA (25.00%), MFI (29.46%), MNF (30.36%), SH (23.18%), and DAP (26.79%).The research achieves success as 6 students exhibit discipline improvements exceeding 20% between cycles I and II, surpassing the initial goal of 2 students. In conclusion, efforts to enhance discipline through group tutoring for Class XI.IPS students at SMA NEGERI 39 JAKARTA have proven successful, exceeding set targets and contributing to a more disciplined student body.